1992
DOI: 10.1128/mcb.12.4.1698
|View full text |Cite
|
Sign up to set email alerts
|

A novel endothelial cell surface receptor tyrosine kinase with extracellular epidermal growth factor homology domains.

Abstract: Endothelial cell surfaces play key roles in several important physiological and pathological processes such as blood clotting, angiogenic responses, and inflammation. Here we describe the cloning and characterization of tie, a novel type of human endothelial cell surface receptor tyrosine kinase. The extracellular domain of the predicted tie protein product has an exceptional multidomain structure consisting of a cluster of three epidermal growth factor homology motifs embedded between two immunoglobulinlike l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
1
7

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(175 citation statements)
references
References 67 publications
4
162
1
7
Order By: Relevance
“…Although Tie1 was isolated more than a decade ago, 18 no ligand had been found to activate it. Recently, Saharinen et al demonstrated that COMP-Ang1 stimulated Tie1 phosphorylation in cultured endothelial cells.…”
Section: Circulation Research July 8 2005mentioning
confidence: 99%
“…Although Tie1 was isolated more than a decade ago, 18 no ligand had been found to activate it. Recently, Saharinen et al demonstrated that COMP-Ang1 stimulated Tie1 phosphorylation in cultured endothelial cells.…”
Section: Circulation Research July 8 2005mentioning
confidence: 99%
“…These paracrine factors downstream of Shh signaling interact with receptors on endothelial cells 40 and parasympathetic neurons and their projections 7,41 to preserve the microvasculature and parasympathetic innervation, which leads to the restoration of salivary gland function likely by improving blood supply and activating the cholinergic receptor muscarinic 1 (Chrm1)/heparin-binding EGF-like growth factor (HB-EGF) pathway with acetylcholine to promote proliferation of Chrm1 + epithelial cells in both acini and ducts of adult salivary glands. 42,43 Further investigation of other responses triggered by transient Hh activation, beneficial or harmful to restoration of the salivary gland, will improve the efficacy of this approach and facilitate its potential clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The family of fibroblast growth factor receptors (FGFRs) consist of at least four tyrosine kinases that share significant structural homology (Jaye et al, 1992;Partanen et al, 1992;Johnson and Williams, 1993).…”
Section: Introductionmentioning
confidence: 99%